A pharmacovigilance study in patients of chronic non-infective respiratory diseases attending outpatient department of pulmonary medicine in a tertiary care teaching hospital - Gaidhane, Sanket S.; Khobragade, Akash A.; Joshi, Abhijeet; Chavan, Monisha S.; H. V., Likith; Chaware, Akshay A. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Adverse drug reactions (ADR) are the known dangers of any medicinal therapy. They are not only responsible for increasing the mortality and morbidity but also for multiplying the health care expenditure. It is important to monitor the adverse effects of the drugs in the patients on treatment for chronic non-infective respiratory diseases attending OPD of pulmonary medicine in a tertiary care teaching hospital Methods: The study was single-centric, non-randomized and observational hospital-based study which was carried out for a period of 1 and a half years in JJ Hospital. The patients who were included in the study suffered from either of the 4 diseases-Chronic obstructive pulmonary disease (COPD), asthma, bronchiectasis or interstitial lung diseases (ILD). Data were analyzed by using Microsoft excel sheet. Based on the outcome of modified Hartwig and Siegel severity assessment scale, ADRs were grouped into various severity categories. Results: One hundred and thirty-two number of ADRs were seen in 69 out of 352 patients (19.6 %) of the study population. The occurrence of ADR was found slightly higher in males i.e., 53.62% as compared to females i.e., 46.38%. The patients who were on treatment for ILD showed highest percentage of ADRs i.e., 57.89% which is followed by bronchiectasis (17.39%), COPD (16.17%) and lastly asthma (10.26%). The ADRs belonging to GIT system were highest in number i.e., 80. The most frequently occurring ADR in the study was palpitation which occurred in 14 cases i.e., 20.29%. Out of 132 ADRs observed, 96 i.e., 72.73% belonged to the mild category and 36 ADRs i.e., 27.27% belonged to the moderate category. Not a single severe ADR was found in the study. Conclusions: It was found that 19.6% of the patient population suffered from ADRs, which is a considerable number. It is essential that health care professionals should support ADR monitoring process for the safety of the medicinal product. Proper implementation of ADR monitoring will help to reduce the harmful effects by early detection of drug safety problems in patients, assessing the risk-benefit in an individual and the population, improving the selection, rational use of drugs through the provision of timely warning to healthcare professionals.